An Excellent Solid Acid Catalyst Derived from Microalgae Residue for Fructose Dehydration into 5‐Hydroxymethylfurural. Issue 4 (25th January 2019) - Zhang, Jianghua; Yang, Shasha; Zhang, Zhenxin; Cui, Li; Jia, Jin; Zhou, Dayong; Zhu, Beiwei
Abstract: An environmentally benign carbonaceous solid acid was synthesized from microalgae residue discarded after biodiesel production. Thereafter, the as‐synthesized carbonaceous solid acid was used for catalytic dehydration of fructose into 5‐hydroxymethylfurural (5‐HMF). Various techniques such as X‐ray diffraction, N2 adsorption‐desorption, scanning electron microscopy, Fourier transform infrared, Raman, X‐ray photoelectron spectroscopy and pyridine adsorption etc were conducted to elucidate the structural and acidic properties of the solid acid so as to build the structure‐performance relationship. The results suggested that large amounts of ‐SO3 H, phenolic ‐OH and ‐COOH groups were grafted onto the investigated material and most of the surface acid sites were assigned to strong Brönsted acid sites. In screening tests with other commercial catalysts, the as‐prepared sample presented excellent catalytic activity with 76.65±2.53% yield of 5‐HMF under aqueous conditions. The dehydration of fructose in dimethyl sulfoxide‐water biphasic system was also tested, affording the 5‐HMF yield as high as 93.84±1.12%. This work provides an efficient and selective solid acid from biodiesel waste and might shed light on an alternative catalyst for highly efficient production of 5‐HMF instead of homogeneous catalysts. Abstract : A novel carbonaceous solid acid with large amounts of strong Brönsted acid sites was synthesized from defatted microalgae residue. The as‐prepared solid acid was investigated as a highly selective, efficient, recyclable and environmentally benign catalyst for 5‐HMF production from fructose in pure water. Noticeably, the 5‐HMF yield was up to 93.84±1.12% in DMSO‐water biphasic system. This work might shed light on an alternative catalyst for highly efficient production of 5‐HMF instead of homogeneous catalysts.